Reduction of the Coefficient of Friction of Steel-Steel Tribological Contacts by Novel Graphene-Deep Eutectic Solvents (DESs) Lubricants - Ignacio Garcia; Silvia Guerra; Juan de Damborenea; Ana Conde (Lubricants, 2019)
Deep eutectic ionic liquids (DES) possess similar properties to conventional ionic liquids (ILs). However, ILs cannot be considered as environmentally friendly compounds due to both its processing and synthesis, which could have significant polluting effects. On the contrary, deep eutectic solvents (DESs) can be biodegradable, non-toxic, and have a lower price than most ILs, making them potentially useful in a wide variety of advanced technological applications, such as tribology. On the other hand, graphene has recently been proposed as an extremely promising lubricant due to its combination of mechanical properties and chemical stability as well as its “green„ character. In the present paper, graphene flakes (≈250 nm) have been used as an additive to DES composed of choline chloride (ChCl)-urea, ChCl-ethylene glycol, and ChCl-malic acid. According to the results, the addition of 1 wt% graphene reduces friction coefficient (COF) and, notably, prevents adhesive wear, reducing wear rate on steel-steel sliding contacts.